VALUE RELEVANCE OF MANDATORY DISCLOSURE EMPIRICAL STUDY IN INDONESIAN PUBLIC COMPANIES - Abdul Hafizh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The objective of this study is to investigate the value relevance effects of mandatory disclosure in measuring firm value in Indonesian public companies. This study uses price model, i.e. stock price as a firm value. Value relevance is measured by earnings per share and book values per share,while mandatory disclosure is measured by index disclosure. The value relevance effect of mandatory disclosure is measured by relating variable earnings per share and book values per share with index disclosure. Regression analysis on sample of 219 firm-years from 2011 to 2012 is employed to test the hypothesis. Those samples are taken from Indonesian Stock Exchange (IDX) in all sectors. The result of the present research shows that mandatory disclosure decreases the relevancies of earnings per share. Meanwhile, mandatory disclosure is increasing the relevancies of book value per share. Keyword: Value relevance, earnings per share, book value per share, stock price, mandatory disclosure.